Low tolerability of carbamazepine in psychiatric patients may restrict its clinical usefulness. - Elphick, M; Lyons, F; Cowen, P (1988)
There are reports of prophylactic efficacy of carbamazepine (CBZ) in manic depres sives when compared with placebo and chlorpromazine. Following a successful open pilot study by one of the authors, an attempt was made to compare carbamazepine and lithium carbonate in a double-blind, crossover trial, each patient being assigned to take each drug for 9 months in random order. However, of the first 14 patients to take carbamazepine four were withdrawn because of drug rashes and another two because of other adverse effects. The trial was discontinued, and a casenotes survey of 50 consecutive psychiatric patients who had been prescribed carbamazepine for mood disorders was then carried out, to establish the tolerability of the drug in clinical practice. Of these, 22 per cent had suffered dizziness, nausea or unsteadiness despite slow introduction of doses. Drug rashes occurred in 16 per cent of patients within the two weeks of starting treatment. A further 14 per cent had other unwanted effects. In total, 36 per cent of the patients had the drug stopped because of adverse effects. With regard to efficacy, in those taking the drug for more than 4 weeks, clinicians reported a definite or probable advantageous effect in 62 per cent of the sample, definite or probable lack of effect in 19 per cent and no opinion in 19 per cent. This low tolerability is not in accordance with previous reports of 2-6 per cent incidence of drug rashes and 10 per cent overall intolerance in neurological patients. We conclude that tolerability is a major drawback to the use of carbamazepine in some groups of psychiatric patients, although all the side- effects were reversible. However, clinical impressions suggested that in a number of patients no other therapeutic strategy was as effective in preventing mood swings.